Pendampingan Pemanfaatan Lingkungan Sebagai Laboraturium Alam dan Sumber Belajar pada Guru-Guru SD Di Kabupaten Jayapura - Kaigere, Daud; Ali, Aisyah (J-Abdimas Cenderawasih, 2024)
This Community Service activity aims to provide experience and techniques in utilizing the surrounding environment as a laboratory and analyzing curriculum relevance and integrating it in learning. The participants of this activity are elementary school teachers in Jayapura Regency. The methods used include lectures, training, and mentoring. The use of the environment as a natural laboratory and learning resource is always available and never runs out. Learning resources that utilize the surrounding environment do not require large costs. This community service activity was attended by 21 teachers from representatives of 10 schools spread across Jayapura Regency. The activity lasted for 2 days, including assistance in identifying curriculum that can be developed into learning that integrates the environment as a natural laboratory and learning resource. The results of the activity showed that the participants were very enthusiastic in participating in the training and mentoring. The resulting products are curriculum analysis, especially Learning Outcomes and Basic Competencies related to the integration of the surrounding environment as a learning resource, as well as learning tools.